Average Error: 0.0 → 0.0
Time: 12.7s
Precision: 64
\[{\left(1 - t\right)}^{3}\]
\[{\left(1 - t\right)}^{3}\]
{\left(1 - t\right)}^{3}
{\left(1 - t\right)}^{3}
double f(double t) {
        double r1968971 = 1.0;
        double r1968972 = t;
        double r1968973 = r1968971 - r1968972;
        double r1968974 = 3.0;
        double r1968975 = pow(r1968973, r1968974);
        return r1968975;
}

double f(double t) {
        double r1968976 = 1.0;
        double r1968977 = t;
        double r1968978 = r1968976 - r1968977;
        double r1968979 = 3.0;
        double r1968980 = pow(r1968978, r1968979);
        return r1968980;
}

Error

Bits error versus t

Try it out

Your Program's Arguments

Results

Enter valid numbers for all inputs

Derivation

  1. Initial program 0.0

    \[{\left(1 - t\right)}^{3}\]
  2. Final simplification0.0

    \[\leadsto {\left(1 - t\right)}^{3}\]

Reproduce

herbie shell --seed 1 
(FPCore (t)
  :name "pow(1-t,3)"
  :precision binary64
  (pow (- 1 t) 3))